Lessons from the 2018 International Symposium on Alternatives Assessment: Advances and Reflections on Practice and Ongoing Needs to Build the Field. (29th October 2019) - Tickner, Joel; Simon, Rachel; Jacobs, Molly; Rudisill, Cathy; Tanir, Jennifer; Heine, Lauren; Spencer, Pamela; Fantke, Peter; Malloy, Tim; Edwards, Sally; Zhou, Xiaoying
ABSTRACT: Alternatives assessment is gaining traction as a systematic method to support the informed substitution of chemicals of concern. The 2nd International Symposium on Alternatives Assessment, on 1–2 November 2018, convened nearly 150 professionals from government agencies, industry, consultant firms, academia, and advocacy organizations to advance a greater understanding of the evolving methods, practices, and challenges in the use of alternatives assessment. This article reviews highlights and lessons from the symposium, including 1) notable advances in methods, 2) shared insights from practitioners on best practices as well as inherent tensions and challenges, and 3) research and practice needs in the field that can be addressed by organizations such as the newly launched Association for the Advancement of Alternatives Assessment. Being interdisciplinary in nature, the establishment of educational frameworks across disciplines and inclusion of diverse expertise in hazard and exposure assessments, life cycle impacts considerations, design principles, and economic and engineering evaluations will ensure continued growth of the field. Integr Environ Assess Manag 2019;00:1–8. © 2019 SETAC Key Points: Over the coming years, the science and practice of alternatives assessment must evolve yet stay true to the ultimate goal of remaining responsive to emerging market and policy drivers, by supporting a transition to safer, more sustainable chemicals, materials, products, and processes. Several of the needs within the field create tension, requiring the field to growth thoughtfully to remain comprehensive yet efficient and effective, successfully linking necessary theoretical and foundational research with pragmatic application and practice. These objectives can be served by developing guidance and standards of practice, increasing data and decision transparency, and creating more comprehensive support programs to build capacity by engaging a broad set of scientists and practitioners.